ETNOEKOLOGI MASYARAKAT GAYO: PERAN HUKUM ADAT DAN NILAI RELIGIUS DALAM KONSERVASI IKAN DEPIK (RASBORA TAWARENSIS) DI DANAU LUT TAWAR - Hendra Yulisman; Yuri Gagarin; Cut Intan Evtia Nurina; Fitrah Asma Ulhusna; Samsul Muarrif; Adelia Ayura (Jurnal Prasasti Ilmu, 2026)
The Gayo people inhabiting Central Aceh have a very strong tradition of local wisdom in utilizing and managing the Lake Lut Tawar area, especially regarding the presence of Depik fish. The purpose of this study is to identify and describe the construction of customary law and ethnoecological knowledge of the Gayo people regarding the rules and limitations of natural resource exploitation in the Lake Lut Tawar ecosystem. The research method used is a qualitative method. Data collection techniques were carried out through open in-depth interviews. The subjects of this study were members of the Majelis Adat Gayo (MAG) for the 2024-2029 period. Interview data were analyzed using the Miles and Huberman interactive model through three stages: data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Gayo people have a strong ethnoecological construction in water conservation, implemented through a 25-meter fishing zoning restriction and the use of environmentally friendly traditional fishing gear (dedesen). The main findings reveal a very strong integration between customary law and religious values ​​(the concept of Fiqh al-Bi'ah), in which fishermen strictly adhere to the prohibition on fishing during religious times (Friday prayers and Tarawih prayers). This compliance is not based on fear of positive state law, but rather driven by spiritual obedience and respect for the Sarak Opat and Pawang Lut institutions (edet memegeri hukum).